Avaliação de tecnologia educativa audiovisual da fisiologia da lactação no conhecimento e na percepção das mulheres da autoeficácia em amamentar - Ribeiro, Polyana de Lima (2023)
Objective: To evaluate whether the audiovisual educational technology of lactation physiology promotes women's knowledge and perception of self-efficacy in breastfeeding. To evaluate the suitability and appearance of the video clip by the puerperal women. To identify barriers and facilitators for the use of this technology by postpartum women. Method: A quasi-experimental before-and-after study was conducted with postpartum mothers of two public hospitals joint lodging in southern Brazil. A pretest and immediate post-test were administered in person to 156 postpartum mothers, and a delayed post-test (7th and 18th day after the first collection) was conducted over the phone with 75 postpartum mothers. An assistive technology assessment instrument (ATAI) and validation of appearance of educational health technologies (IVATES) were applied, along with a test on anatomophysiological aspects of lactation knowledge and the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF), in addition to questions about the barriers and facilitators to the use of knowledge. Results: The educational technology was evaluated as appropriate (mean = 1.93 SD = 0.12), and appearance validity was excellent (IVA = 0.97). When analyzing individual participant responses in relation to different test administration moments, no consistent pattern of knowledge gain was observed; however, a significant difference was found between the three moments. The median score on the test before the intervention was 5 points (IQR 4-7), after the intervention it was 9 (IQR 7-10), and during the phone stage, it was 7 points (IQR 6-8) (p < 0.001 for all comparisons). The median percentage of knowledge gain from moment 1 to moment 3 was 33% (IQR 0-75%). When BSES-SF data were analyzed, the SE data of the 75 participants who took part in all stages of the study were compared, revealing a median of 66 (IQR 60-69) in the first moment, a median of 67 (IQR 62-70) in the second moment, and a median of 69 (IQR 66-70) in the third moment. A significant increase in SE was observed with each administration of the BSES-SF (p < 0.001). In multiple comparisons, it was evident that there was no significant variation from time 1 to time 2 (p = 0.165), but there was between time 2 (post-intervention) and time 3 (p = 0.048), and between time 1 (pre-intervention) and time 3 (p < 0.001). The average percentage increase in SE was 6.3% (SD 12.9%). Out of 5 participants who started with an average SE, 4 ended the study with high SE, and out of the 70 participants with high SE, they remained in that category, with no significant change in SE category (p = 0.125). There was no relationship between SE gain and participant characteristics. Conclusion: The use of translated knowledge about lactation physiology through a validated educational audiovisual technology promotes knowledge gain and perception of SE among postpartum mothers. This gain did not show statistical significance in association with participants' education, marital status, and occupation, nor with type of delivery, breastfeeding experience, and number of prenatal consultations, indicating that the video clip has the potential to be used with accessible translated knowledge to mediate health education for this target population.